The Indonesian Strategy to Achieve Universal Health Coverage through National Health Insurance System: Challenges in Human Resources - Adyas, Atikah (Kesmas, 2021)
Many countries are currently trying to achieve universal health insurance coverage in order to provide health protection for their population. Indonesia has received a strong political commitment to implement national health insurance including government support to finance the poor. The implementation of comprehensive national health insurance requires human resources, each of which has a role in fighting for noble goals for the welfare of all people. This paper is taken from the experience of Indonesia and several other countries as well as guidelines that can be used in exploring the role of human resources for the success of the implementation of national health insurance.